Motivation of Private Investors to Stock Market - Д О Стребков (Journal of Economic Sociology, 2010)
The object of this paper is the people who understood the perspectives of stock market and did first steps to become private investors. They have opened discretionary account in Investment Company and got the opportunity to buy and sell stocks and bonds on Russian brokers’ exchanges. On the basis of detailed interviews and questionnaire the author analyzes the structure of the motives that define the choice for stock market as a way of money investment for contemporary Russian brokers.  It was shown in the paper that the variety of motives of beginners and old players on the stock market is very complex and could not be reduced to simple rational material benefits.